PENINGKATAN KETERAMPILAN MENULIS TEKS EKSPOSISI DENGAN METODE INQUIRYDISCOVERY LEARNING DAN PENGGUNAAN MEDIA VIDEO PADA SISWA KELAS VII G SMP NEGERI 3 COLOMADU - Aji, Wisnu Nugroho (MAGISTRA, 2016)
This thesis aims to improve quality of process and result of studentsâ ability in writingexposition text using inquiry discovery learning method and video at seventh grade students in smp n 3colomadu. Based on the observation, the increasing quality of teaching learning process in writingexposition text at the first cycle is 66 % and the second cycle is 75 %. The result of studentsâ ability inwriting exposition text at the first cycle is 62.5 % and the second cycle is 84.4 %. The conclusion of thisresearch is the implementation of inquiry discovery learning and using video can increasing quality oflearning process and studentsâ result in writing exposition text at seventh G grade students in smp negri3 colomadu.Keywords : inquiry discovery learning, Video, Writing skill, Exposition text.